Primary dysmenorrhea: evaluation and treatment pattern among female medical students - Gupta, Sapna; Kaur, Sharminder; Sadiq, Shamiya; Khajuria, Vijay (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Dysmenorrhea is a very common condition in females in fertile age group and its affective and somatic features often limit female mobility which results in loss of work hours. The aim of the study was to evaluate prevalence, severity, drug usage and loss of work days among young female medical students. Methods: The current questionnaire based study was done in Department of pharmacology, GMC Jammu over a period of 3 months. Female students aged between 17-24 years who consented for participation were included. The demographic profile and detailed history of dysmenorrhea was recorded. Results: Out of 342 participants, 218 females (63.7%) had history of dysmenorrhea. Most of the dysmenorrhic females had menarche between 13-14 yrs of age (73.3%) and menstrual cycle of 21-34 days (82.5%), duration of bleeding less than 6 days (91.6%) and had a positive family history of dysmenorrhea (58.7%). Majority of females had mild to moderate features of dysmenorrhea (93.4%). Most common medication was Mefenemic acid alone and in combination (90.5%). Most of the females took self-medication (69.8%) and only 30.2% took medicines on advice of doctor. 71.5% students missed their classes due to symptoms of dysmennorhea. Conclusions: Dysmenorrhea is quite prevalent among college going medical students. Most of them had positive family history. Mefenemic acid and its combination was frequently used to treat symptoms. On an average 1-2days were lost due to dysmenorrhea.